Impacto da Covid-19 no equilíbrio corporal e na qualidade do sono - Melo, Ellen Aguirre de (2024)
COVID-19 caused by the SARS-CoV-2 virus has been presenting prolonged and persistent sequelae months after infection, affecting different systems of the human body and presenting a wide range of symptoms and non-specific physiological changes, such as functional movement disorders and changes in circadian rhythm patterns. Therefore, the objective of this research was to identify the sociodemographic and clinical profile of subjects with Post-COVID-19 Syndrome and evaluate whether the condition alters sleep quality and body balance after 12 months of acute SARSCoV- 2 infection. This research had a quantitative and observational cross-sectional nature. Thirty-six participants, between 18 and 45 years old, six men and thirty women, were included in the study. All participants underwent anamnesis, visual inspection of the external auditory canal, Mini Mental State Examination, Pittsburgh Sleep Quality Index, Foam Laser Dynamic Posturography, Vestibular Evoked Myogenic Potential and Dizziness Handicap Inventory for those with complaints of dizziness. When comparing subjective sleep report with the Pittsburgh Sleep Quality Index, a discrepancy in sleep quality was observed, noting worse sleep quality conditions using the Pittsburgh Sleep Quality Index. The results of the sensory analysis were below reference parameters, in particular, the somatosensory system and visual preference were altered. Vestibular Evoked Myogenic Potentials were within standard limits, with no evidence of statistically significant differences. Regarding the Dizziness Handicap Inventory, the subjects presented low scores. After 12 months of infection, subjects affected by Post-COVID-19 Syndrome demonstrated changes in body balance through sensory analysis, despite the good functioning of the vestibulo-cervical and vestibuloocular reflex pathways. Additionally, the study sample showed problems related to sleep, a common condition in post-COVID-19 Syndrome, observing a direct relation with the latencies and asymmetry index assessed in the potentials.